Congenital adrenal hyperplasia with polycystic ovarian disease: A rare cause of hirsutism - Rasul, Shazia; Dar, Lubna Riaz; Hameed, Abdul (Journal of Pakistan Association of Dermatologists, 2016)
Hirsutism may be defined as presence of terminal hairs in women with a male-like pattern ofÂ distribution. Hirsutism is related to serum androgen and cutaneous sensitivity to other hormones. TheÂ most prevalent causes of hirsutism are polycystic ovary syndrome and isolated hirsutism. NonclassicalÂ congenital adrenal hyperplasia (21-hydroxylase deficiency) and drug induced type are less frequent rather rare causes. Diagnostic evaluations should address identifying etiology and itsÂ associated co-morbidities to properly manage the patients. We present a case of 22-year-oldÂ unmarried female who presented with hirsutism and on detailed evaluation she was diagnosed as aÂ case of nonclassical adrenal hyperplasia and polycystic ovaries. Along with laser hair removal,Â proper treatment of underlying etiology led to reversal of her symptoms.